Telling stories: perspectives on longitudinal writing research - Fishman, Jenn, editor; Kimme Hea, Amy C., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
In Telling Stories, more than a dozen longitudinal writing researchers look beyond conventional project findings to story their work and offer otherwise unavailable glimpses into the logics and logistics of long-range studies of writing.--Provided by publisher.
Storying longitudinal research: relationality and self-reflexivity / Brad Jacobson and J. Michael Rifenburg -- Weaving reflexivity, relationality, and time in a decade-long study of writing development and learning transfer / Dana Lynn Driscoll -- Following participants as leaders in long research / Lauren Rosenberg -- Mission-driven longitudinal research: the public value of telling the stories of two-year college writers / Holly Hassel and Joanne Baird Giordano -- Understanding imbricated contexts: institutional formation and longitudinal writing research / Amy C. Kimme Hea -- Researching for capital: longitudinal research, precarity, and institutional citizenship / Doug Downs, Mark Schlenz, Miles Nolte, and Ashley Rives -- More simple gifts: labor, relationships, and ethics in longitudinal research / Aimee C. Mapes -- The precarious method: longitudinal research and material uncertainty in professional and technical writing studies / Yanar Hashlamon -- Radically longitudinal, radically contextual: growing lifespan writing research / Ryan J. Dippre and Talinn Phillips -- Becoming history / Jenn Fishman -- Epilogue: why we tell stories / Jenn Fishman and Amy C. Kimme Hea.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Academic writing -- Longitudinal studies; College students' writings -- Longitudinal studies; Longitudinal method -- Case studies